Iron Ion‐Doped Tricalcium Phosphate Coatings Improve the Properties of Biodegradable Magnesium Alloys for Biomedical Implant Application. Issue 16 (17th June 2020) - Antoniac, Iulian V.; Filipescu, Mihaela; Barbaro, Katia; Bonciu, Anca; Birjega, Ruxandra; Cotrut, Cosmin M.; Galvano, Ettore; Fosca, Marco; Fadeeva, Inna V.; Vadalà, Gianluca; Dinescu, Maria; Rau, Julietta V.
Abstract: Iron‐substituted tricalcium phosphate (Fe‐TCP) (about 1 wt%) coatings are deposited on biodegradable Mg‐Ca alloys to improve their corrosion resistance. Pulsed laser deposition technique is used for coating preparation. The 2 µm thick coatings are uniformly deposited. (Ca+Fe)/P ratio for the Fe‐TCP coatings is close to the stoichiometric value. Coated and uncoated Mg‐Ca alloys are subjected to electrochemical tests to investigate the influence of the coatings on their corrosion resistance in simulated body fluid (SBF). Tafel curves corresponding to coated and uncoated Mg‐Ca alloy samples in SBF show that the most electropositive corrosion potential is reached for the Fe‐TCP‐coated Mg‐Ca deposited at 300 °C. From the obtained and calculated values of the electrochemical parameters it follows that this sample possesses the best characteristics: it has the smallest porosity and the highest protective efficiency in SBF. Equine adipose tissue‐derived mesenchymal stem cells are used for 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide test and osteogenic differentiation study. Microbiology tests are performed with Escherichia coli (E. coli) (Gram − ) and Staphylococcus aureus (Gram + ) bacteria strains. The Fe‐TCP‐coated Mg‐Ca deposited at 300 °C is characterized by the best cytocompatibility and good ability to inhibit the growth of E. coli and is recommended for biomedical implant applications. Abstract : Iron‐substituted tricalcium phosphate coatings deposited on biodegradable Mg‐Ca alloys by pulsed laser deposition technique improve their corrosion resistance and reduce the degradation rate. Coating deposited at 300 °C is characterized by a good cytocompatibility and a good ability to inhibit the growth of E. coli and is recommended for biomedical implant applications.